ABOUT ONE OF THE GENERALIZATION OF AILAR’S $φ(m)$ FUNCTION - Aslanian, L. Kh. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2003)
In connection with the problems of supplement in this work the generalization of Ailar’s $φ(m)$ functions is introduced and a formula is got for the definition of the value of this generalized function.
Keywords: generalization of Ailar’s functions; problems of supplement